Using telephone logs instead of databases to accurately estimate neurosurgical on-call workload. (June 2013) - Mukerji, N.; Vergani, F.; Hassan, F.; Dubois, J.; Metcalfe, S.; Cowie, C.; Mitchell, P.
Abstract Background. Maintenance of on-call referrals databases is on the rise in neurosurgical units across the UK and helps provide data to estimate workload. We hypothesize that these databases underestimate the workload and propose the use of the number of telephone calls to the on-call registrar as an easily obtainable and valid measure of workload. Methods. Data were obtained from a referrals database maintained and completed by the neurosurgical registrars and the hospital switchboard telephone logs. Data were analysed using JMP 8.0.2 (SAS Institute, Cary, NC). Results. We found a large degree of disparity between the number of phone calls and the number of recorded referrals. The median number of phone calls to the on-call registrar per day was 78 (Interquartile range 59–106); but the median number of recorded referrals was 12 (Interquartile range 8–16). 49.8% of the calls were received out-of-hours (1700–0800 and weekends) and the maximum number of calls was received on a Friday. Data derived from both sources (database and switchboard logs) showed a close visual correlation. Conclusion. We argue that on-call logs are an easily obtainable, reliable and internally validated measure of activity. We recommend the use of such data in other centers to establish the nature of on-call activity and tailoring of the rotas to comply with current guidance to provide a mix of service and training.